Volatility Spillover, Hedging and Portfolio Diversification Between Oil Market and S&P Sectoral Indices - Gencyurek, Ahmet Galip; Ekinci, Ramazan; Agan, Busra (Ege Univ, Fac Economics & Admin Sciences, 2023)
The study aims to analyze the volatility spillover between the oil market (WTI) and the S&P (Stand and Poor's) Energy, Financial, and Industry sector indices through conditional correlation and variance causality. The DCC-GARCH (Dynamic Conditional Correlation-Generalized Autoregressive Conditional Heteroscedasticity) and Hafner-Herwartz (2006) Variance Causality models were used to analyze the daily data for the period between January 3, 2012 and December 31, 2019. The results indicate a positive time-var ying conditional correlation between the oil market and sector indices. In addition, the hedge ratios and risk-minimizing portfolio weights (which are vital for investors) have been calculated based on these data. The cheapest hedging transaction with the oil market occurs in the financial sector, while the most expensive one occurs in the energy sector. It has also been determined that volatility is transmitted from the sector indices to the oil market. This situation means that the S&P sector indices play a leading role (resource of information-emit information) in volatility spillover. The results provide important information to researchers, investors, and policymakers.
Keywords: Oil Market; Sector Indices; Multivariate GARCH; Variance Causality; Spillover